2011
DOI: 10.1098/rsif.2011.0258
|View full text |Cite
|
Sign up to set email alerts
|

Human-like external function of the foot, and fully upright gait, confirmed in the 3.66 million year old Laetoli hominin footprints by topographic statistics, experimental footprint-formation and computer simulation

Abstract: It is commonly held that the major functional features of the human foot (e.g. a functional longitudinal medial arch, lateral to medial force transfer and hallucal (big-toe) push-off ) appear only in the last 2 Myr, but functional interpretations of footbones and footprints of early human ancestors (hominins) prior to 2 million years ago (Mya) remain contradictory. Pixel-wise topographical statistical analysis of Laetoli footprint morphology, compared with results from experimental studies of footprint formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
167
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(177 citation statements)
references
References 56 publications
(126 reference statements)
7
167
3
Order By: Relevance
“…A second study showed that the shapes of the Laetoli footprints were significantly different from those of footprints created by humans walking with a strongly BHBK gait [14]. Both of these studies based their interpretations of the Laetoli tracks on the observation that the BHBK footprints in their simulations and experiments were relatively deep under the forefoot and shallow under the heel [14,15]. Here, we directly studied experimentally produced chimpanzee footprints and found that this pattern does not hold.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A second study showed that the shapes of the Laetoli footprints were significantly different from those of footprints created by humans walking with a strongly BHBK gait [14]. Both of these studies based their interpretations of the Laetoli tracks on the observation that the BHBK footprints in their simulations and experiments were relatively deep under the forefoot and shallow under the heel [14,15]. Here, we directly studied experimentally produced chimpanzee footprints and found that this pattern does not hold.…”
Section: Resultsmentioning
confidence: 99%
“…One analysis used forward dynamics computer simulations based on human muscle activity data to generate hypothetical pressure distributions beneath a lower limb and foot modelled based on skeletal dimensions of A. afarensis [15]. Based on dissimilarities between these hypothetical pressure distributions and the topography of the Laetoli footprints, the authors concluded that a BHBK gait could not have created the Laetoli prints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian bipedalism traces back 230 million years to their dinosaur ancestors [1,2], whereas hominins have a significantly shorter bipedal history of at least 3.6 million years [3,4]. Although both humans and birds move bipedally, there are a number of morphological disparities, which will affect their locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, animals with low body temperatures may have undergone greater adaptations, or more adaptation events, than those with higher body temperatures. Early human ancestors began bipedal walking 3.66 million years ago [14], likely because bipedal walking requires 75% less energy than quadrupedal walking [15]. Bipedal walking became the defining feature of the earliest hominids, and undoubtedly represented a drastic lifestyle change through adaptation; therefore, the low body temperature of humans might be due to our adaptation to bipedal locomotion.…”
Section: During Evolution Some Animals Emerged From and Later Returnmentioning
confidence: 99%